2018
DOI: 10.1051/matecconf/201817202001
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of heat transfer in phase change material using graphite-paraffin composites

Abstract: Abstract. Phase change materials (PCMs) are energy storage materials which can be used for maintaining a controlled thermal environment for various applications in earth and space. PCMs are used in advanced technologies in aerospace cooling applications like heat exchangers and heat pipes for re-entry vehicles and spacecraft. Paraffin is a phase change material (PCM) commonly used for energy storage-related applications. Paraffin wax exhibits slow thermal response due to low thermal conductivity value (~0.2 W/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Notably, the PCM C -10%GP composite demonstrated a narrower phase transition temperature range in comparison to both the PCM C (0%GP) and PCM C -20%GP composites. This reduced range signifies the effectiveness of incorporating graphite powder into the PCM, specifically emphasizing the optimal ratio for reducing the heat absorption and heat release time of the PCM [40]. Especially during the endothermic process, the PCM C -10%GP composite exhibited a 35.94% lower melting time in comparison to plain PCM.…”
Section: Thermal Analysis Of the Pcm-gp Compositesmentioning
confidence: 99%
“…Notably, the PCM C -10%GP composite demonstrated a narrower phase transition temperature range in comparison to both the PCM C (0%GP) and PCM C -20%GP composites. This reduced range signifies the effectiveness of incorporating graphite powder into the PCM, specifically emphasizing the optimal ratio for reducing the heat absorption and heat release time of the PCM [40]. Especially during the endothermic process, the PCM C -10%GP composite exhibited a 35.94% lower melting time in comparison to plain PCM.…”
Section: Thermal Analysis Of the Pcm-gp Compositesmentioning
confidence: 99%
“…The efficiency of the collector was improved with paraffin wax and Nano-composite by (6.9% and 8.4%), respectively. Sathiyaraj et al [16] experimentally improved the PCM thermal conductivity for thermal storage (use paraffin wax as PCM) by boosting it with graphite powder. The results showed that the paraffin/graphite powder compound had better performance in heat transfer due to the high thermal conductivity (300 to 550 W/mK).…”
Section: Introductionmentioning
confidence: 99%